THE EFFECT OF THE STORYTELLING METHOD ON THE PUBLIC SPEAKING SKILL OF CADETS SURABAYA AVIATION POLYTECHNIC - Siti Julaihah (Jurnal Penelitian)
The ability of public speaking is very much needed by cadets in the face of competition in the world of work, so an appropriate method is needed to improve the public speaking skills of cadets, one of which is by using the storytelling method. This study aims to find out the effect of the storytelling method on the public speaking skills of cadets of the Aircraft Engineering study program at the Aviation Polytechnic of Surabaya. This study uses the design of the Explanatory Survey Method. The results showed that the effect of storytelling on the public speaking skills of cadets was in the high category. This means that more and more cadets in public speaking practice using the storytelling method will have an impact on their public speaking practice